Analysis of the Social Vulnerability Index for the Mount Agung Eruption Disaster, Karangasem Regency, Bali - Muhammad Arus Samudro; Fadlilatin Nailah; Astri Rino Okvitasari; Retno Syahriawati Dewi; Arisessy Maharani Mulananda; Desta Rifky Aldara (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
Indonesia is an archipelagic country located between the continents of Asia and Australia as well as the Indian and Pacific Oceans. Geographically, Indonesia is located between 6°N-11°S and 95°-141°E. The location of the mountains in Indonesia varies greatly because this country has many islands with diverse topography. The social vulnerability index for volcanic eruptions includes the parameters of population density, vulnerable age ratio, sex ratio, disabled population ratio, and poor population ratio. This research aims to determine the value of the social vulnerability index in each area within the eruption radius of Mount Agung if an eruption occurs. The methods used in data collection are secondary and primary data collection methods. The method for processing data is quantitative descriptive statistical data analysis called factor analysis and scoring analysis based on PERKA BNPB No. 2 of 2012 with the results of a risk level scoring for each parameter of the social vulnerability index. The results obtained from this research are the risk level of the social vulnerability index in the Karangasem district. The highest social vulnerability index is in the sub-districts of Banyakdem and Karangasem with a score of 26 and the lowest sub-district is Kubu sub-district with a score of 15. The Sedimen sub-district with a score of 25, the Manggis and Selat sub-districts with a score of 24, the Abang sub-district 20, and the Rendang sub-district 18.